Meningkatkan Aktivitas dan Pemahaman Siswa Kelas VIII melalui Discovery Learning dan Media Wordwall dalam Pembelajaran Iman kepada Rasul Allah Swt - Shofi, Ajmal Ramzani Nasywa (Maliki Interdisciplinary Journal, 2025)
This research aims to improve the learning outcomes of students in grade VIII-D MTsN 1 Malang in learning the Moral Faith material for the Prophet of Allah SWT through the application of the discovery learning method with jigsaw techniques and the use of online wordwall media. The subjects of this study are 34 students in grades VIII-D, consisting of 12 males and 22 females in the 2024/2025 Academic Year. This research is a Class Action Research (PTK) consisting of two cycles. The first cycle uses the discovery learning method with a jigsaw technique, while the second cycle uses an impromptu quiz based on online wordwall media. The results of the study showed that in the first cycle as many as 80% of students achieved learning completeness, and in the second cycle only 6 students could not answer correctly. This shows that there is an increase in student learning outcomes through the learning strategies applied.